High-resolution atomic force microscopy as a tool for topographical mapping of surface budding - Sbarigia, C.; Tacconi, S.; Mura, F.; Rossi, M.; Dinarelli, S.; Dini, L. (Frontiers in Cell and Developmental Biology, 2022)
Extracellular vesicles (EVs) are membranous nanoparticles secreted by almost all cell types. Reflecting the physiopathological state of the parental cell, EVs circulate in all body fluids, reaching distant cell targets and delivering different bioactive cargoes. As biological carriers, EVs influence their microenvironment altering cellular responses, being considered promising biomarkers for both physiological and pathological conditions. EVs are heterogeneous in terms of size and composition, depending on cell type and exposure to stimuli, and different methods have been developed to characterize their morphological, biophysical, and biochemical features. Among them, electron microscopy (EM) is the main technique used, however, the lack of standardized protocols makes it difficult to characterize EVs with a good reproducibility, thus using multiple approaches may represent a way to obtain more precise information. Furthermore, the relationship between architecture and function, not only in a molecular, but also in a cellular level, is gaining growing emphasis, characterizing morphometric parameters may represent a distinct, but effective approach to study the physiopathological state of the cell. Atomic force microscopy (AFM), may represent a promising method to study in detail EVs dynamics throughout the cell surface and its variations related to the physiological state, overcoming the limits of EM, and providing more reliable information. In this study, human neuroblastoma SH-SY5Y cell line, a cellular model to investigate neurodegeneration and oxidative stress, has been used to perform a comparative morphological and quantitative analysis of membrane budding and isolated large vesicles-enriched (microvesicles-like vesicles; MVs) fraction from control or oxidative stressed cells. Our main goal was to build up a methodology to characterize EVs morphology and spatial distribution over the cell surface in different physiological conditions, and to evaluate the efficacy of AFM against conventional EM. Interestingly, both microscopy techniques were effective for this analysis, but AFM allowed to reveal a differential profiling of plasma membrane budding between the physiological and the stress condition, indicating a potential relationship between mechanical characteristics and functional role. The results obtained may provide interesting perspectives for the use of AFM to study EVs, validating a morphometric approach to understand the pathophysiological state of the cell related to EVs trafficking.